Supplementation of Spirulina platensis in feed and water for the performance of broiler - Billah, MM; Debi, MR; Al-Mamun , M; Islam, KMS (Bangladesh Journal of Animal Science, 2022)
Spirulina is multicellular, blue green algae, which contains protein (50-70%), carbohydrate (12-13%), fat (6%) fat and substantial amount of minerals, vitamins, carotenoids and some fatty acids. Considering nutrient content and prospective health benefits, an experiment was conducted with 144-day old broiler (Cobb-500). Chicks were divided into 6 groups having 24 birds in each (8 per cage). Experimental groups were (1)-0.25% vitamin in feed, (2)-0.25% vitamin in feed + 0.5g/L Spirulina in water from laboratory, (3)-0.25% vitamin in feed + 0.5g/L commercial Spirulina in water, (4)-0.0% vitamin + 0.25% Spirulina in feed, (5)-0.25% vitamin + 0.25% Spirulina in feed, (6)-0.0% vitamin + 0.0% Spirulina in feed. The diets were iso-caloric (3170Kcal/kg) and iso-nitrogenous (22.7% CP). After 35 days feeding trial body weight was 1263, 1294, 1308, 1338, 1372 and 1188g/bird in group 1, 2, 3, 4, 5 and 6 respectively where numerically higher weight was observed in group 5 and lower in group 6, but overall significant variation observed among the groups (p<0.05). Feed intake was 2475, 2302, 2320, 2311, 2342 and 2378 g/bird in group 1, 2, 3, 4, 5 and 6 respectively (p<0.5). Feed conversion ratio (Kg feed intake/kg live weight gain) was higher in group 6 (2.00) and lower in group 5 (1.70), but was overall significant variation observed among the groups (p<0.05). It may be concluded that Spirulina would be supplemented in feed and water separately or at a time for better performance and health status of broiler. Bangladesh Journal of Animal Science. 51(1):17-24